Total training for Adobe Premiere Pro CS3 essentials - Barbosa, Jason; Hunt, Christopher; Vitner, Eric.; Borrero, Barbara Stilwell; Gemeinhardt, Jamie; Safari eBooks ([Carlsbad, Calif.?] : Total Training, Inc., 2008)
"Total training for Adobe Premiere Pro CS3: Essentials will get you up and running on the fundamental skills in no time. This video series helps you learn how to capture raw video from your camera, edit it into a great piece, and output it to tape, disc and web formats. Along the way you'll learn how to use many of the video and audio effects Premiere Pro has to offer to fix problematic footage and make your content look and sound spectacular. You'll walk away knowing how to create graphics and text titles for your video projects, as well as slideshows."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher.
Title from title frames.
Director, video production, Barbara Ross ; technical director, Richard Lainhart ; art director-executive producer, Brian Maffitt ; cinematographer, Jason Barbosa.
Electronic reproduction.
Keywords: Adobe Premiere; Motion pictures -- Editing -- Data processing; Digital video -- Editing -- Data processing; Electronic books